Faktor Terkait Praktik PHBS Masyarakat Pada Masa Pandemi Covid-19 Di Desa Randuboto Kabupaten Gresik - Siti Zaerina; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: COVID-19 is an pandemic, including Indonesia. PHBS (Clean and Healthy Living Behaviour) is an effort to strengthen the behaviour of a person, group, and community to care for and prioritize health to create a higher quality life. Community participation in efforts to prevent COVID-19 is an important factor in breaking the chain of infection. As 9 July 2020 3 residents have been confirmed positive for COVID-19 in Randuboto Village. Objectives: Therefore this research was carried out to analyze the factors related to PHBS practices durung the COVID-19 pandemic in Randuboto Village, Gresik Regency. Research Metodes: This type of research used in this study is an observational study using a cross sectional approach. The population in this study was the total population of Randuboto Village, Gresik Regency which was recorded as many as 4,006 people. The sampling technique used in this study was snowball sampling. The nimber of samples taken was 108 samples that met the inclusion criteria. The independent variables in this study are the level of knowledge, attitudes, and the availability of supporting facilities for the respondents. The dependent variable in this study is PHBS practices during the COVID-19 pandemic. Results: PHBS practices in Randuboto Village, Gresik Regency during the COVID-19 pandemic showed good practice at 55,6%. This is related to the activity of washing hands with soap and running water, diligently eat healthy foods, regularly do physical activity/ exercise, smoking outside the house, regularly cleaning the neighborhood where I live, regularly leaving the house during the COVID-19 emergency using a mask, frequently visiting public places and being crowded during colds. The majority of respondents were ≤ 25 years old, which was 63,9%, while the majority of respondents education level was Senior High School at 53,7%. The majority of respondents types of work are other at 52,8%. The variable related to the practice of PHBS during the COVID-19 pandemic are the level of knowledge(0,001), attitudes (0,001), and the availability of supporting facilities (0,001). Conclusion: Most of the respondents have a poor level of knowledge, good attitude, availability of adequate supporting infrastructure and good PHBS practices during the COVID-19 pandemic.The practice of PHBS during the COVID-19 pandemic In the environment around Randuboto Village, Gresik regency needs to be improved again, especially in knowledge, as weel as the availability of supporting facilities. It is hoped that the community an also improve personal hygiene such as washing hands regularly and wearing masks when doing activities outside. This is very important to break the chain of spread of the COVID-19